Layer-by-layer polyelectrolyte coated erythrocyte carriers - Heng, Puay Ling. (2011)
This report shows the need to improve the process due to the increased interest in using carrier erythrocytes as drug delivery system. The erythrocytes coated with a polyelectrolyte multilayer provide a simple mean for controlling the burst and subsequent release of bioactive agents. This work aims to improve the efficiency of the process of encapsulating model substance (FITC – dextran) into the carrier erythrocyte and depositing oppositely charged polyelectrolyte (PEs) onto the erythrocyte via layer-by-layer (LbL) deposition method.